Faktor-Faktor yang mempengaruhi Nilai Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia - Dewi Pertiwi Novelita; Nelliyana Nelliyana (Media Bisnis, 2021)
The objective of this research is to obtain empirical evidence that leverage policy, liquidity, profitability, company size, investment policy, sales activity, free cash flow, and corporate growth influence firm value. The population of this research is all manufacturing companies listed in Indonesia Stock Exchange from 2013 to 2016. Sixty-seven manufacturing companies are selected as the research sample using purposive sampling method. This research uses multiple regression method for hypothesis analysis. The empirical result of this research shows that leverage policy, profitability, size, and free cash flow positive influence firm value. However, liquidity, investment policy, sales activity, and corporate growth do not influence firm value.